A novel cross-coupled microstrip bandpass filter with hairpin-DGS resonators using coupling matrix technique - Chetioui Mohammed; Bouasria Fatima; Damou Mehdi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper introduces a new design of a cross-coupled microstrip bandpass filter (MBPF) based on hairpin defected ground structure (DGS) resonators using accurate coupling matrix (CM) technique for microwave communication systems. The paper describes the equivalent circuit of the proposed MBPF based on the DGS equivalent circuit model derived from the equivalent inductance and capacitance which occur due to the perturbation of the current in the ground plane by the presence of the slots. The paper investigates also the different external coupling mechanisms that the feed configuration affects significantly the filter response. In this paper, a four order Chebyshev topology has been adopted for designing the filter to suppress harmonics and achieve a very compact size and a wide stopband with two transmission zeros.